THE CONCEPT OF CHILDREN'S EDUCATION IN ISLAMIC PARENTING BOOK AND THEIR RELEVANCE WITH CHARACTER EDUCATION OF MI/SD AGES - Sofyan, Muhammad; Saefuddin, Asis; Dewi, Karima Yuspiani (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2021)
Educational problems often occur at every level, including the elementary school level. Often found students who have bad morals, it reflects the occurrence of moral and ethical decadence. This happens because in learning only focus on the development of cognitive aspects, even though it must be balanced with the development of affective aspects. Efforts to overcome this are through the implementation of character education and optimizing it for elementary school age children. Educators can imitate the success of the Prophet Muhammad in educating. Therefore, researchers are interested in examining the book Islamic Parenting by Jamal Abdurrahman about the concept of education in children. The method used in this research is library research method using documentation data collection techniques. While the data analysis used is content analysis with data analysis model Milles and Huberman, the steps are data reduction, data presentation and conclusion/verification. The results showed that the concept of child education in the second stage (Age 4-10 years) and education in the third stage (Age 11-14 years) in the Islamic parenting book has relevance to character education for children aged (MI/SD), namely in terms of its integration with the curriculum or subject matter in MI/SD. Of the 10 character values, there are 9 character values that have relevance to character education. In addition, each class has relevance to the Islamic Parenting book.